Solidity properties of neutron-irradiated CdTe epitaxial films - Akobirova, Aziza T.; Brinkevich, Dmitry I.; Vabishchevich, Sergey A.; Halauchyk, Victoryia I.; Lukashevich, Michail G.; Mahsudov, Barot I. (Journal of the Belarusian State University. Physics, 2018)
Investigations of solidity properties (microhardness, chapresist, distruction effective energy, microfragility) of CdTe thin films prepared on CdTe substrate CdTe/CdTe and silicon substrate CdTe/Si and influence of neutron-irradiation on these parameters have been carried out by means of indention and sclerometry methods. It was shown that microhardness increases with strength increasing because of strain deformation. Solidity properties of CdTe/CdTe films close to the bulk substrate, while K1c and γ for CdTe/Si films 3–8 times lower. It was observed that microhardness of CdTe/Si films increases with neutron doze increasing, while for CdTe/Si films – decreases.